Effects of rubber leaf litter vermicompost on earthworm population and yield of pineapple (Ananas comosus) in West Tripura, India - P. S. Chaudhuri; T. K. Paul; Animesh Dey; M. Datta; S. K. Dey (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Rubber leaves are the abundant agro-waste and pineapple, the most economically important fruit crop in Tripura. So, in our present study, different amounts of rubber leaf vermicompost have been applied to the soils of pineapple plantation to determine their effects on earthwormsâthe soil ecosystem engineers, coupled with the vegetative growth and yield of pineapples. Methods During 30 months of field trial (2010â2012) in ICAR regional station, Lembucherra, West Tripura, the control plot (T0) received no fertilizer, while experimental plots were fertilized with four different amounts of vermicompost viz. T1 (5 tons ha-1 year-1 ), T2 (10 tons ha-1 year-1 ), T3 (20 tons ha-1 year-1 ) and T4 (30 tons ha-1 year-1 ). Results A significant (p.05) but gradual increase in density (up to T3 treatment) and biomass (up to T4 treatment) of earthworms were recorded with the increasing amounts of vermicompost. During the second year, average length and width of leaves, number of leaves per plant, plant girth, fruit weight, fruit yield and fruiting percentage were highest in the T3 plot compared to other treated plots and control. Conclusion The present study reveals that crop yield is very much related to the particular concentration of vermicompost, beyond the level of which production declines and increase in vegetative growth, fruit weight and fruiting percentage of pineapple are strongly linked with the soil pH, av. P, av. K, clay content and the earthworm density of soils.